2013
DOI: 10.2106/jbjs.k.01291
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Local Anesthetics on Human Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells likely play a key role in healing following surgical procedures such as microfracture and ligament reconstruction. If local anesthetics are used following joint surgery, selection of an agent with low toxicity toward mesenchymal stem cells, such as ropivacaine, may maximize tissue healing potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 2 publications
2
56
1
1
Order By: Relevance
“…1-3, 9-12 While the main therapeutic targets of LAs are voltage-gated sodium channels in neuronal cells, there is potential for them to have off-target effects on other cells in the microenvironment, including MSCs and macrophages. Several studies have demonstrated anti-inflammatory effects to LAs.…”
Section: Introductionmentioning
confidence: 99%
“…1-3, 9-12 While the main therapeutic targets of LAs are voltage-gated sodium channels in neuronal cells, there is potential for them to have off-target effects on other cells in the microenvironment, including MSCs and macrophages. Several studies have demonstrated anti-inflammatory effects to LAs.…”
Section: Introductionmentioning
confidence: 99%
“…Ropivacaine and bupivacaine had limited toxicity in human mesenchymal stem cells, but lidocaine has shown to reduce mesenchymal stem cell viability. 7 Finally, the association of HA with local anesthetics reduced their cytotoxicity with bupivacaine but not lidocaine, suggesting different mechanisms of injury between the two compounds. 8 Esterification of steroids, producing crystals of various sizes, is another structural option that makes them water insoluble, slowly degraded by the synovial esterase enzymes, with a delayed absorption and a more prolonged local antiinflammatory effect.…”
Section: Resultsmentioning
confidence: 98%
“…21 In a similar study, when MSCs were exposed to bupivacaine, ropivacaine, or lidocaine, administration of lidocaine was found to have a significant cytotoxic effect. 22 Moreover, when MSC monolayers were exposed directly to bupivacaine, ropivacaine, and mepivacaine, all three showed time-and concentration-dependent cytotoxic effects. 23 Based on this in vitro work, it is clear that local anesthetics may have a deleterious effect on the function of MSCs.…”
Section: Potential Implications Of Anesthetics On Mscsmentioning
confidence: 97%
“…21 Dans une étude semblable, lorsque des CSM ont été exposées à la bupivacaïne, à la ropivacaïne ou à la lidocaïne, on a observé que l'administration de lidocaïne avait un effet cytotoxique significatif. 22 En outre, lorsque des monocouches de CSM ont été exposées directement à de la bupivacaïne, de la ropivacaïne ou de la mépivacaïne, ces trois agents ont tous démontré des effets cytotoxiques dépendants de la durée et de la concentration. 23 Sur la base de ces travaux in vitro, il est clair que les anesthésiques locaux pourraient avoir un effet délétère sur la fonction des CSM.…”
Section: Les Voies De Transmission Thérapeutiques Des Csmunclassified